Impacts of pH and plant growth media on growth of plant growth promoting rhizobacteria (PGPR), UPMB10 development - Surimin, Adilah; Shamsuddin, Zulkifli (Program Pemindahan Ilmu - Kementerian Pendidikan Malaysia, 2013)
Plants grown hydroponically require plant growth media containing the necessary plant nutrients for optimum growth. The media pH needs to be at optimum level for growth of the plant. Plant growth media also affects growth of Plant Growth Promoting Rhizobacteria (PGPR). A study was conducted to investigate response of PGPR to different pH range (4.0, 5.0 and 6.0) and plant growth media (Hoagland and Vitagrow) under laboratory condition in 250 mL of conical flask on shaker at 250rpm with temperature 25- 28˚C. Growth of PGPR UPMB10 was observed daily by using optical density (O.D600) on the first day (D1) until day 6 (D6). The result showed a descending order in growth at following pH in Hoagland solution; pH 4.0>pH 6.0>pH 5.0, while in the Vitagrow; pH 4.0>pH 5.0=pH 6.0. Bacterial growth in Hoagland solution relatively more rapid change and unstable pattern growth compared to those grown in Vitagrow. In general, bacterial growth higher at lower pH (pH 4.0) compared to increased pH (pH 5.0 and 6.0).